The direct connections of the C2 dorsal ganglion in the brain stem of the squirrel monkey: a preliminary investigation - Fitz-Ritson, Don E. (1979)
The purpose of this investigation was to observe the possible anatomical connections of C2 dorsal root with brain stem nuclei. Labelled amino acids (leucine, glycine, proline), were injected into the dorsal root of C2 of a squirrel monkey. The animal was allowed to survive for 20 hrs. and after, sections of the spinal cord and brain stem were subjected to autoradiographic methods. Direct connections were observed in Lamina II, VII, VIII of the spinal cord; the hypoglossal nucleus, medial vestibular nucleus, lateral cuneatus nucleus and lateral parvocellular reticular formation. Possible anatomical and physiological correlates are explored in relation to the importance of the upper cervical area and its control mechanisms.